Residential exposure to motor vehicle emissions and the risk of wheezing among 7-8 year-old schoolchildren in Nicosia, Cyprus - Middleton, Nicos; Nicolaou, Nicolaos C.; Pipis, Spiros D.; Zeniou, Maria; Kleanthous, Savvas; Demokritou, Philip; Koutrakis, Petros; Yiallouros, Panayiotis K. (My University, 2009)
Background: First-time investigation into the frequency of asthmatic symptoms among Cypriot children showed increased prevalence in the capital compared to all other areas. Exposure to traffic pollutants have been repeatedly shown to be associated with a range of cardiorespiratory effects. Differences in asthma prevalence on an island the size of Cyprus may reflect such environmental factors. Objective: To investigate the association between residential exposure to traffic pollution and the risk of asthmatic symptoms within the city of Nicosia. Methods: The addresses of participating children in Nicosia were geo-coded (N = 1,735) and levels of exposure were assessed using both (a) distance-based and (b) emissions-based indicators e.g. estimated levels of traffic pollutants at all roads within a pre-defined distance around the residence. Odds ratios of self-reported symptoms in relation to exposure were estimated in logistic regression models adjusting for person-based risk factors and co-morbidity as well as intra-school clustering. Results: Up to 2-fold differences in symptoms were observed; however, increased risk seemed to concentrate at distances less than 50 m from a main road and/or only among those experiencing the highest levels of cumulative exposure. Associations persisted after adjusting for other risk factors. While the direction of effect was apparent at longer distances, differences were not statistically significant. Adjusted odds ratios for current wheezing were 2.33 (95% CI 1.27, 4.30) amongst the quartile of participants exposed to the highest levels of particulate matter (PM) at all roads 50 m of their residence and 2.14 (95% CI 1.05, 4.35) for levels of nitrogen oxides (NOx). Conclusions: Children with the highest vehicular emissions burden around their residence seem to be at higher risk of reporting symptoms. However, due to the small number of children residing at close proximity to main roads and with no evidence of effect at longer distances, this alone would not explain the generally higher prevalence observed in the urban areas in Nicosia.
Keywords: Geographical Information System; Main Road; Emission Inventory; Personal Exposure; Parental Smoking